If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-5y-y=7
We move all terms to the left:
13-5y-y-(7)=0
We add all the numbers together, and all the variables
-6y+6=0
We move all terms containing y to the left, all other terms to the right
-6y=-6
y=-6/-6
y=1
| 46-2x=8x-16 | | 11a^2-5a+11=0 | | w+-3=-4 | | 7.2+5.2f=8.76 | | -3(2t+1)=21 | | x-22+1=4x-53 | | x-0,7x=2550000 | | 10x2-8x-6=0 | | 12.5z–6.4=–8z+3(1.5z–0.5) | | 2(y-1)+y=5(-2y+3)-2(y+3) | | 3(2y+5)=30-4y | | 8-3x=128-5x | | -2y+14=-5(y-7) | | -4b+7=-5b | | 10(s-6)=103 | | 20d+60=300 | | 800x+300=500x+1000 | | -3(3x-6)=-9(x-2) | | -4a^2+4a=5 | | 58(a-2)=100 | | 2x+x+30+x-35=515 | | w+|-2.8|=4.8 | | (u-4)*9=90 | | 9p=-171 | | -4+x÷-2=-23 | | y+-21.03=-34.51 | | 5b^2=-3b-1 | | (e+5)*3=48 | | (-x)*9x=32 | | w+|−2.8|=4.3w+|−2.8|=4.3w | | -5r^2+4r=1 | | 53-3x=24x+16 |